A new look at water transport regulation in plants. Issue 1 (2nd July 2014) - Martínez‐Vilalta, Jordi; Poyatos, Rafael; Aguadé, David; Retana, Javier; Mencuccini, Maurizio
Summary Plant function requires effective mechanisms to regulate water transport at a variety of scales. Here, we develop a new theoretical framework describing plant responses to drying soil, based on the relationship between midday and predawn leaf water potentials. The intercept of the relationship (Λ) characterizes the maximum transpiration rate per unit of hydraulic transport capacity, whereas the slope (σ) measures the relative sensitivity of the transpiration rate and plant hydraulic conductance to declining water availability. This framework was applied to a newly compiled global database of leaf water potentials to estimate the values of Λ and σ for 102 plant species. Our results show that our characterization of drought responses is largely consistent within species, and that the parameters Λ and σ show meaningful associations with climate across species. Parameter σ was ≤1 in most species, indicating a tight coordination between the gas and liquid phases of water transport, in which canopy transpiration tended to decline faster than hydraulic conductance during drought, thus reducing the pressure drop through the plant. The quantitative framework presented here offers a new way of characterizing water transport regulation in plants that can be used to assess their vulnerability to drought under current and future climatic conditions.